Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT. Jasa Raharja (Persero) Cabang Solok - Marisanda Marisanda; Rasidah Nasrah; Hendri Irawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research was conducted by PT. Jasa Raharja (Persero) Solok Branch, which is located at Jl. KH. Ahmad Dahlan Pandan Near Solok City. While the research time is estimated in June 2022 to find out and analyze Compensation for Employee Performance at PT. Jasa Raharja (Persero) Solok Branch. The type of research that will be carried out is descriptive quantitative research, in which this study seeks to find out a clearer picture of leadership style and compensation for employee performance at PT. Jasa Raharja (Persero) Solok Branch. While the form of research is Causal Research, (cause and effect) where there are independent variables that affect the dependent variable. The number of samples in this study used total sampling where the entire population was sampled, namely all employees of PT. Jasa Raharja (Persero) Solok Branch as many as 52 people. Based on the results of the simple linear regression analysis carried out, the regression equation Y = 9.311 + 1.128X means that if the compensation value is fixed or equal to zero (0) then the employee's performance will be worth 9.311 and if the compensation is increased by 1 unit then the employee's performance will increase by 1.128, p. This proves that compensation has a positive influence on the performance of employees of PT. Jasa Raharja (Persero) Solok Branch can be accepted. The result of the R2 (R square) value is 0.612 or 61.2%, this indicates that Compensation (X) has an effect on Employee Performance at PT. Jasa Raharja (Persero) Solok Branch of 61.2%. While the remaining 38.1% is influenced by other variables such as career development, training and employee motivation which are not included in this study. Based on the t test, the calculated t value is also greater than t table, namely 9.019> 1.6751 and the value is not significant 0.000< 0.05 then there is an effect of compensation on employee performance at PT. Jasa Raharja (Persero) Solok Branch